GPER-1 in chronic hepatitis B. Issue 1 (1st January 2020) - Kandemir, Bahar; Ates, Selma; Kurutas, Ergül Belge; Durduran, Yasemin; Erayman, Ibrahim; Bitirgen, Mehmet
ABSTRACT: Estrogen has a significant role in regulating cell proliferation, growth, migration, aging, and many disease states. Estrogen shows its effects through estrogen receptors alpha, beta, and G protein-coupled estrogen receptor 1 (GPER1). The aim of this study is to evaluate serum GPER1 levels and its relationship with fibrosis score in chronic hepatitis B patients. The cases were selected from two university hospitals and consisted of patients who had not previously been treated for hepatitis B, were over 18. Quantitative sandwich enzyme immunoassay technique was used for measuring the serum levels of GPER1. The data evaluated were analyzed by using the statistical tests. Out of the 65 cases; 26 (40%) had hepatitis B, 39 (60%) were controls. Patients underwent liver biopsy. GPER1 levels were significantly high in Hepatitis B group (p < 0.001). Out of the 26 hepatitis B patients; 21(80, 8%) had low-stage fibrosis, 5(19, 2%) had high-stage fibrosis. When the GPER1 level was ≥017600000 the sensitivity, specificity, positive predictive value, and negative predictive value for the hepatitis B patients were found to be 96%, 87, 7%, 96%, and 92, 8%, respectively. GPER levels have shown high expression in patients with chronic hepatitis B.